PERBANDINGAN MODEL PEMBELAJARAN TALKING STICK DAN NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR IPA SISWA DIKELAS VIII SMP KARTIKA I-4 - Mustika Piliang, Fenny (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2021)
This study aims to determine the differences in student learning outcomes using Talking Stick and NHT in class VIII of SMP Kartika I-4 Pematangsiantar on the Human Digestive System material in the 2020/2021 Academic Year. This study is a type of quasi-experimental research (Quasi Experiment) that is given different treatments in each class. Samples were taken using cluster random sampling technique, obtained class VIII-1 was used as experimental class I using the Talking Stick learning model with a total of 23 students, while class VIII-3 was used as experimental class II using the NHT learning model with a total of 23 students, research data analysis, finding the average value, standard deviation, homogeneity test, normality test and t test. From the results of the study, the average value in the experimental class I was 85 while the student learning outcomes in the experimental class II were 80. From the results of hypothesis testing using the t test, t count (3.63) was obtained > t table (2.00), thus the alternative hypothesis (Ha) was accepted and (Ho) was rejected, meaning there was a significant difference in student learning outcomes using Talking Stick and NHT on the Human Digestive System material for class VIII of SMP Kartika I-4 Pematangsiantar in the 2020/2021 Academic Year.